Abundance and physiognomic characteristics of woody natives in a sub-urban talar forest remnant extensively invaded by exotic vegetation: Native trees and neoecosystems - Alcalde, Leandro; Rodríguez-Allo, Luisina (Revista de Biología Tropical, 2024)
Introduction: The talares are small xerophytic forests dominated by the trees Celtis tala and Scutia buxifolia, which are characteristic of the pampas in the Northeast of Buenos Aires Province, Argentina. Talares coexist with areas facing significant urban and agricultural pressures, leading to their impoverishment, fragmentation, and even local extinction. Objective: To characterize a resilient talar patch within a suburban forest invaded by exotic vegetation to identify the patterns and processes currently affecting native woody species. Methods: The forest (55 ha) was divided into seven sampling sites. We assessed the abundance and physiognomic variables of native woody species through random searches (approach 1). For exotic woody species, we used a combination of transects and grids within the forest and on adjacent streets (approach 2). The analyses included descriptive statistics, index calculations, and comparisons through confidence interval establishment and Chi-square tests with Yates' correction. Results: Total sampling time per team member was 118.5 h for approach 1 and 48 h for approach 2. Two native species dominate the studied talar patch: C. tala (88 %) and S. buxifolia (11 %), while other native woody species were extremely rare (1 %). Exotic woody species were dominant structurally and numerically. We observed variations of C. tala and S. buxifolia height between forest stands, most common under 3 m in height. The Mantle Index indicated light competition due to shading caused by fast-growing, large exotic species. Damage due to falling eucalyptus branches was observed only in C. tala, although at a low percentage. S. buxifolia had 20 % and C. tala 15 % of individuals with a shrub-like form with some cases being variable among forest stands. We propose several manageent strategies aimed at favoring native species over exotics. Conclusion: The studied forest is a hybrid ecosystem with neo-ecosystem traits, which implies a series of conservation problems for the remaining native woody species present. It is highly valuable for the conservation of talares, particularly for one of its most emblematic species, S. buxifolia, which is virtually absent outside the forest area.